Pendekatan Pembelajaran Mendalam untuk Mengembangkan Kreativitas dan Keterampilan Menulis di Era Digital - Anita Candra Dewi (Journal of Humanities, Social Sciences, and Education, 2025)
The digital era presents new challenges and opportunities in education, particularly in developing students' creativity and writing skills. The deep learning approach is one relevant strategy to address these demands. This approach emphasizes conceptual understanding, critical reflection, and active emotional and cognitive engagement in the learning process. Through deep learning, students are not only able to memorize but also able to construct knowledge, innovate, and express creative ideas in meaningful writing. This literature review aims to examine the role of the deep learning approach in enhancing creativity and writing skills in the digital era. The research method used a literature review approach by reviewing various national and international journals from 2019–2025. The results of the study indicate that deep learning integrated with digital technology can foster reflective thinking skills, increase originality of ideas, and strengthen writing skills through the use of digital media such as blogs, collaborative platforms, and AI-based applications. Thus, the application of this approach is not only relevant in the context of 21st-century learning but also an effective strategy for creating a creative, critical, and digitally literate generation.